Poisson-type approximation for sums of 1-dependent indicators - Kelmelytė, Jūratė; Čekanavičius, Vydas (Lietuvos matematikos rinkinys, 2008)
The sum of 1-dependent indicators is approximated by two-parametric Poisson type signed measure. Estimates are obtained for the local and total variation norms.